Climate risk assessment for Cannabis spp. in Santa Catarina State, Brazil - Camargo, Priscila; Pandolfo, Cristina; Bosco, Leosane Cristina (Agrometeoros, 2024)
Interest in the medicinal use of Cannabis spp. has been increasing due to scientific evidence demonstrating its therapeutic potential. However, in Brazil, agronomic studies on its cultivation are incipient. This study aimed to perform a climate risk analysis for the cultivation of Cannabis spp. in the state of Santa Catarina (SC), Brazil. From the bibliographic review and the systematization of meteorological data of the state, the critical parameters of photoperiod (< 14 h), probability of occurrence of minimum temperatures (< -6°C) and thermal sum (< 2500 GDD) were considered. The Cannabis spp. may be cultivated in all regions of SC, provided that the technical guidelines according to the inherent risks in each region are observed. Within the ten-day period from 33 to 8 (November 21 to March 20), the photoperiod and absolute minimum air temperature criteria were not restrictive in any region of the state. For the critical parameter of thermal sum, in regions where the risk is elevated due to a thermal sum below 2500 Growing Degree Days (GDD), this limitation may be mitigated by advancing the timing of plant establishment. This research offers valuable insights for researchers, policymakers, and those interested in cultivating Cannabis spp. in Brazil, with a strategic perspective aimed at fostering initiatives that consider the potential for producing Cannabis spp. in the Santa Catarina territory.